Phytochemistry and Vasorelaxant activity of some plants used traditionnaly against high blood pressure in Benin - TOKOUDAGBA, Kossi Jean-Marie Denis; Gandonou, Clément; SCHINI-KERTH, V. (My University, 2018)
The ethnobotanical survey conducted in Zou and Colline regions in February 2015 yielded twelve plants used traditionally against high blood pressure (hypertension) by the local population.. The phytochemical analysis and the biological screnning allowed to identify two plants more active (Carissa eduliss Apocynaceae, Diodiascandess Rubiaceae) than the active plant identified during a previous biological screnning carried out in 2006 [1]. These two active plants are very rich in phenolic compounds and have the same phytochemical profile in contrast to the others plants which have different phytochemical profile. The active plants have an antioxidant activity closer to that of the standards used. Some plants of the sample have a very strong antioxidant activity but are not active. The vasorelaxant activity of these two plants (Carissa edulis Apocynaceae, Diodia scandess Rubiaceae) is superior to the vasorelexant activity of Parkia biglobosa (Mimosaceae) [1]. Through this study, two new plants traditionally used against hypertension are retained among the twelve selected plants.
Keywords: Medicinal plants; arterial hypertension; vasorelaxant activity